Post-industrial mining communities: aspects on geoecology of quality of life - Offenberg, Iulian; Frățilă, Cristian Ovidiu; Iliaș, Ioana Tiberia; Iliaș, Nicolae; Offenberg, Alexandra; Radu, Sorin Mihai; Fetiniuc, Valentina (Національний технічний університет "Харківський політехнічний інститут", 2023)
The multidisciplinary nature of quality of life calls for appropriate definitions of the concept. Although it is specific to the field of sociology, it appears more and more often in ecology, economy, health, climatology, etc. The phenomenon of metamorphosis thus involves the different fields with activities that produce natural and technical changes. The modification of natural systems and their transformation due to natural-technical causes, characteristic of post-industrial mining areas, brings the new fields of research closer to the geographical environment. The analysis of the quality of life of the communities in these areas involves a transdisciplinary approach (between and within various disciplines as well as beyond any of them) to understand the p hysiognomy and health of landscapes, respectively the ecology of landscapes loaded with life resources. Through the lens of geotectonic movements in the last period of time, in addition to safe underground mining, ensuring security and health in public and private above-ground spaces requires the need to analyze the real situation, primarily in public institutions, in the public and private health system (hospitals, ambulatories). This paper briefly reviews the geoecology of quality of life, focusing on the most important definitions of the concept and highlighting the elements applicable to post-industrial mining areas.

Мультидисциплінарний характер якості життя вимагає відповідного визначення цього поняття. Хоча це специфічно для галузі соціології, воно все частіше з'являється в екології, економіці, охороні здоров'я, кліматології тощо. Таким чином, феномен метаморфоз охоплює різні сфери діяльності, які спричиняють природні та технічні зміни. Модифікація природних систем та їх трансформація внаслідок природно-технічних причин, характерна для постіндустріальних гірничодобувних територій, наближає нові галузі досліджень до географічного середовища. Аналіз якості життя громад у цих районах передбачає трансдисциплінарний підхід (між різними дисциплінами та всередині них, а також за межами будь-якої з них), щоб зрозуміти фізіономію та здоров'я ландшафтів, відповідно, екологію ландшафтів, завантажених життєвими ресурсами. Через призму геотектонічних рухів в останній період часу, окрім безпечного підземного видобутку корисних копалин, забезпечення безпеки та здоров'я в публічних і приватних надземних просторах потребує необхідності аналізу реальної ситуації, насамперед у державних установах, державній та приватній системі охорони здоров'я (лікарні, амбулаторії). У цій статті коротко оглядається геоекологія якості життя, зосереджуючись на найважливіших визначеннях концепції та висвітлюючи елементи, застосовні до постіндустріальних гірничих районів.
Постіндустріальні гірничі спільноти: аспекти геоекології якості життя
Keywords: mining; communities; geoecology; life; видобуток корисних копалин; громади; геоекологія; якість життя